Propuesta para la planeación y control de la producción de productos personalizados en la empresa Ecoempaques Corrugados en Bogotá. (2021)
The main objective of the case study described in the following article is to propose production planning and control systems for the company Ecoempaques Corrugados. For its diagnosis, the cross-function flow diagram tools, VSM, Ishikawa will be used, which allow obtaining the projection of real data of the current problems, giving way to the elaboration of MPS, capacities, sales forecasts, among others, having into account the who ?, when? and how much? of the resources are necessary for the manufacture of the boxes with personalized design, as a result of this the improvement plans, strategies and action plan are developed in order to explain to the interested parties its logic and operation, so that they understand the importance of correct planning and control of production.